West Africa during the Atlantic slave trade : archaeological perspectives - DeCorse, Christopher R. (Bloomsbury academic collections. Story of the trasatlantic slave trade., 2016)
Surveying archaeological data from West Africa, with sites ranging from the Senegambia to the Cameroon, this volume focuses on data from about 1500, a time period that witnessed dramatic transformations in African political and social life.